HOW COOPERATIVE LEARNING MODELS EFFECT LEARNING OUTCOMES IN VOCATIONAL EDUCATION? - Alamsyah, Amalia Putri; Wahono, Puji; Rachmadania, Rizki Firdausi (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2024)
This research aims to determine the effect of using the Team Games Tournament (TGT) type cooperative learning model on the learning outcomes of class XI Office Management and Business Services (MPLB) students in the Office Management Concentration 1 subject at State Vocational Schools 3 Jakarta. The research uses a quantitative approach with quasi-experimentation. This study involved 71 class XI students from the MPLB department. This study uses a saturated sampling method, which is included in the non-probability sampling method category. The results of the research show that the TGT type cooperative learning model influences student learning outcomes. The results of hypothesis testing using the Independent Sample t-test show that the result is 0.009 < 0.05, and the calculated t value is greater than the t table, namely 2.701 > 1.995. Posttest calculations show that the experimental class using the TGT learning model obtained an average score of 80.08 which was higher than the average score of the control class using conventional learning methods of 75.51.